THE CONCEPT OF AL HISBAH AND ITS IMPLEMENTATION IN INDONESIA IN THE PERSPECTIVE OF DA'WAH - Alkhotob, Imam Taufik (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2023)
Da'wah activities through efforts to prevent evil ( nahi munkar ) among humans are known as al-Hisbah . The practice of munkar occurs everywhere and is carried out openly. This requires maximum prevention efforts from various parties. Both from the side of the state and also from society. However, the facts on the ground show that the implementation of the al munkar causes many problems (madharat). This study used a qualitative research method with a library research approach, also called a qualitative literature review. The author conducts an in-depth (philosophical) study to find principles in the application of hisbah that originate from the books of the Salaf and Khalaf scholars. The conclusion from the results of this study states three things: First, the concept of hisbah in Islam is comprehensive. This concept does not only speak of monitoring one area but all things, which includes the goodness left behind and the evil that is seen, with its four pillars: al muhtasib, al muhtasab 'alaihi, al muhtasab fihi, and al ihtisab. Second, the authors have formulated 14 important rules that become guidelines in the practice of hisbah across the state. Third, the author has also formulated 17 important principles in the practice of hisbah in society.